THE EFFECT OF EMPLOYEE EMPOWERMENT, ORGANIZATIONAL CULTURE, COMPENSATION, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN PT. PERKEBUNAN NUSANTARA III - Andri Putra Panjaitan; Syahbuddin Hasibuan; Ihsan Effendi (ZILLZELL MEDIA PRIMA, 2023)
Study This aim To know the influence empowerment of employees, culture organization, compensation, and the environment Work to performance employee executor at PT. Perkebunan Nusantara III. This study uses a quantitative descriptive method. This research was conducted at PTPN III. The population in this study was 17,368 employees implementing oil palm plantations P III. TPNThe number of samples in this study were 174 samples from 20 plantations of PTPN III entities. The independent variables in this study consisted of employee empowerment (X 1 ), organizational culture (X 2 ), compensation (X 3 ), and work environment (X 4 ), while the dependent variable was employee performance (Y). Determination of the sample was carried out by purposive random sampling. Data analysis was performed using multiple linear regression analysis. The study results show that employee empowerment positively and significantly affects employee performance. Organizational culture has a positive and significant effect on employee performance. Compensation has a positive and significant effect on employee performance. The work environment has a positive and significant effect on employee performance. Simultaneously employee empowerment, organizational culture, compensation, and work environment significantly affect the performance of implementing employees at PT. Perkebunan Nusantara III.